Philippe Thomas declines his identity : an exhibit in one act and three sets - Bosser, Daniel; Jaret, Émeline ([S.l.] : Occasional Papers, 2014)
"First authorised translation of ‘Daniel Bosser, Philippe Thomas décline son identité’, a book about modernism and modalities of display, first published by Galerie Claire Burrus, Paris, in 1987. The book was part of a performative talk given only twice by the French conceptual artist Philippe Thomas (1951–95). ... Consistent with Thomas’ practice to distinguish his name from authorship, this book is attributed to Daniel Bosser, the collector who acquired the piece"--From a post by Occasional Papers on vimeo.com (viewed February 2016). 1
Published on the occasion of 'Marginalia' (Raven Row, London, December 2014 - January 2015)
boek
Keywords: Thomas, Philippe